Income Level and Its Role in Human Development in The Souran Sub - District (Journal of Hama University, 2021)
The standard of living has a very important impact on the progress of any country in the world, and any decrease in this level is considered a warning for officials and planners to reconsider future issues and find appropriate solutions. That is why countries in the world are interested in providing the best standard of living for their residents by providing everything that meets their needs in terms of health and education services.The research aims to study and analyze the level of income and spending patterns in the Souran sub-district and its developmental importance to give us a realistic picture of consumption and spending patterns in the development of some areas of development in the sub-district.Three main axes were researched: the first axis represented the level of income and the factors affecting the average per capita income in the sub-district, the second axis focused on spending and consumption patterns in the sub-district, and the third axis dealt with the features of human poverty and levels of human development in the sub-district. The research was concluded to a link between the improvement of the individual's income and improvement in development in mind, where the improvement contributed to increasing the average of per capita of quotas and reduce poverty levels and improved health and education levels in the individual  in the mind.